Analisis Stabilitas Sheet Pile Kali Sono Kota Madiun - Aji, Seno; Rohman, Rosyid Kholilur; Cahyono, Setiyo Daru (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2020)
Abstract— Slope slides can occur if the specific gravity of the land working as the driving force is greater than the shear stress that serves as a restraining force. To prevent landslides there are several methods that can be used, one of them is using sheet pile as a soil barrier. Besides working to hold the soil, the sheet pile also functions to prevent the entry of water into dug pits, so it is very good to be used at the edge of the sea or river. The formulation of the problem that arises is how the value of active and passive soil pressure on the sheet pile, as well as how the suitable CPC Sheet Pile specifications are used in this study. The research method used is geotechnical analysis for sheet pile retaining walls. Based on soil data and calculation analysis, the value of active soil pressure on sheet pile is 104.06 kN / m and the value of passive soil pressure is 206.19 kN / m2. The CPC Sheet Pile specification used is Type W-600A, 15 meters long with Mcrack = 50.6 Ton.meter. Keywords—: Slope slides; sheet piles; the value of active and passive; geotechnical analysis.